Zika virus - A new chalenge for obstetricians and gynecologists. Continuation - Pacheco Romero, José (2016)
It has been only a few weeks since we published in this Journal the review “Zika virus – a new challenge for obstetricians and gynecologists”(1). There are now daily news on new characteristics of the virus infection, concerning mainly on the infection of the fetus, sexual transmission and spread of the virus in the Americas.